Bioaktivitas Metabolit Sekunder dari Genus Dipterocarpus - Nalle, Halena A.; Lulan, Theodore Y. K.; de Rozari, Philiphi; Ola, Antonius R. B. (Universitas Nusa Cendana, 2022)
Research has been conducted with the title